Chemical variations of loess from the Chinese Loess Plateau and its implications. Issue 8 (28th April 2023) - Xiao, Yuanyuan; Wu, Shengying; Sui, Peishan; Niu, Yaoling; Sun, Weidong; Wang, Guodong; Kong, Juanjuan; Shao, Fengli; Wang, Xiaohong; Gong, Hongmei; Duan, Meng; Huang, Zihang
ABSTRACT: The Chinese Loess Plateau (CLP) is the largest loess deposit on Earth with expansive surface-exposed source rocks of varying origins, ages, and history. Here, we present abundances of elements on representative loess and palaeosol samples from seven classic sections of the CLP. Most elements, including soluble elements (e.g. Rb and Cs), show significant correlations with La or Al2 O3 . These correlations indicate that these elements are hosted or absorbed in particle minerals during weathering, transport, and deposition (e.g. mica, K-feldspar, and clay minerals). These new observations allow the use of La/X ('X' being the element of interest) and the estimated La abundance of 31 ppm in the model upper continental crust (UCC) to estimate the abundances of other elements. The results show higher Cs (Cs = 6.7 ± 1.2 ppm), lower transition metals, Ba, and Ga. Given the high CaO and presence of carbonate in UCC rocks of both vast western China (the primary source for the CLP) and eastern China, we propose that these updates on the element abundances represent a refined model for the carbonate-bearing UCC.